The Influence of Mastery Motivation Towards Social-Emotional Competence in Early Childhood - Anayanti Rahmawati; Mareyke Maritje Wagey Tairas; Nur Ainy Fardana (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
Establishing interpersonal relationships is an important task of early childhood. Harmonious interpersonal relationships will be achieved well if children have social-emotional competence, namely the ability to manage their own condition in order to maintain positive relationships with others. This study aims to determine the influence of mastery motivation towards social-emotional competence. This type of research is quantitative. The total sample was 417 children aged 5-6 years. Collecting data using a questionnaire filled out by teachers and parents. Data analysis using linear regression method with t-test obtained t test results of 3.776 and sig of 0.000. Based on these results, it can be concluded that there is an influence of mastery motivation towards social-emotional competence. The magnitude of the influence of mastery motivation was 3.3%. Taking into account the effect of mastery motivation on low social-emotional competence, it is hoped that teachers and parents can foster mastery motivation so that social-emotional competence can be achieved more optimally.